2014
DOI: 10.1007/s13277-013-1429-0
|View full text |Cite
|
Sign up to set email alerts
|

S-1-based therapy versus S-1 monotherapy in advanced gastric cancer: a meta-analysis

Abstract: This study aimed to derive a more precise estimate of the prognostic significance of S-1-based therapy over S-1 monotherapy in patients with advanced gastric cancer (AGC), including overall survival (OS) time, progression-free survival (PFS) time, objective response rate (ORR), and adverse events (AEs). Studies stratifying OS, PFS, ORR, and AEs in AGC patients in an S-1-based therapy versus an S-1 monotherapy setting were eligible for analysis by systematic computerized PubMed, Embase and Cochrane Library sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…All the included meta-analyses indicated that S-1 combination therapy was superior to monotherapy in terms of OS and PFS [7, 20, 23]. As for RR, two of them favored S-1 combination therapy in objective RR [7, 23] while another one meta-analysis indicated that S-1 was favorable regarding overall RR [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the included meta-analyses indicated that S-1 combination therapy was superior to monotherapy in terms of OS and PFS [7, 20, 23]. As for RR, two of them favored S-1 combination therapy in objective RR [7, 23] while another one meta-analysis indicated that S-1 was favorable regarding overall RR [20].…”
Section: Resultsmentioning
confidence: 99%
“…All the included meta-analyses indicated that S-1 combination therapy was superior to monotherapy in terms of OS and PFS [7, 20, 23]. As for RR, two of them favored S-1 combination therapy in objective RR [7, 23] while another one meta-analysis indicated that S-1 was favorable regarding overall RR [20]. All the meta-analyses demonstrated that S-1 combination therapy was associated with higher incidence of AEs or grade 3-4 toxicity event [7, 20, 23].…”
Section: Resultsmentioning
confidence: 99%
“…Results from a meta-analysis indicated that S-1-based therapy showed significant ORR, longer PFS, and longer OS than S-1 monotherapy, although with higher incidence of grade 3 to 4 neutropenia. 5 In a retrospective trail that compared S-1 plus cisplatin (SP) to capecitabine plus cisplatin (XP), SP and XP were associated with similar efficacy and safety in AGC patients. 16 However, for elderly HER2-positive ACG patients, trastuzumab might be a better treatment option than S-1.…”
Section: Discussionmentioning
confidence: 99%
“… 3 S-1, as a new novel oral fluoropyrimidine agent, has already been confirmed to show promising anticancer efficacy for AGC. 4 , 5 Because the S-1 plus cisplatin (SP) chemotherapy regimen is accepted as the standard therapy for AGC in Japan, 6 this combination has been studied in several completed clinical trials. 7 , 8 However, this regimen consistently produces high incidences of grade 3 to 4 hematological toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, Wu JR et al [1] conducted a meta-analysis to derive a precise estimation of the prognostic significance of S-1-based therapy over S-1 monotherapy in patients with advanced gastric cancer (AGC) including overall survival (OS) time, progression-free survival (PFS) time, objective response rate (ORR), and adverse events (AEs). Before their results can be accepted, we have several worthwhile queries that we would like to communicate with the investigators.…”
mentioning
confidence: 99%